2016
DOI: 10.1007/8904_2016_5
|View full text |Cite
|
Sign up to set email alerts
|

Classical Galactosaemia and CDG, the N-Glycosylation Interface. A Review

Abstract: Classical galactosaemia is a rare disorder of carbohydrate metabolism caused by galactose-1-phosphate uridyltransferase (GALT) deficiency (EC 2.7.7.12). The disease is life threatening if left untreated in neonates and the only available treatment option is a long-term galactose restricted diet. While this is lifesaving in the neonate, complications persist in treated individuals, and the cause of these, despite early initiation of treatment, and shared GALT genotypes remain poorly understood. Systemic abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 113 publications
1
25
0
Order By: Relevance
“…Therefore, there is an urgent need to elucidate the mechanisms of impairment affecting these patients in order to improve their quality-of-life. Various groups have made notable advances in this aspect through studies of patients and model organisms (Haberland et al 1971; Bohles et al 1986; Nelson et al 1992; Berry et al 2001; Kushner et al 2010; Berry 2011; Potter et al 2013; Rubio-Agusti et al 2013; Coss et al 2014; Jumbo-Lucioni et al 2014; Timmers et al 2015; Jumbo-Lucioni et al 2016; Maratha et al 2016; Timmers et al 2016). In this study, we aimed to establish if our GALT-deficient mouse model is a suitable animal model for the pathophysiology studies of the ataxia phenotype in human patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need to elucidate the mechanisms of impairment affecting these patients in order to improve their quality-of-life. Various groups have made notable advances in this aspect through studies of patients and model organisms (Haberland et al 1971; Bohles et al 1986; Nelson et al 1992; Berry et al 2001; Kushner et al 2010; Berry 2011; Potter et al 2013; Rubio-Agusti et al 2013; Coss et al 2014; Jumbo-Lucioni et al 2014; Timmers et al 2015; Jumbo-Lucioni et al 2016; Maratha et al 2016; Timmers et al 2016). In this study, we aimed to establish if our GALT-deficient mouse model is a suitable animal model for the pathophysiology studies of the ataxia phenotype in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…In model systems studies, Jumbo-Lucioni et al reported that co-removal of the dGALK (galactokinase) gene or sugarless overexpression corrected the aberrant glycosylation of the neuromuscular junction (NMJ) extracellular synaptomatrix carbohydrates and the impaired coordinated movement in a Drosophila model of Classic Galactosemia (Jumbo-Lucioni et al 2014), further solidifying the pathogenic roles of galactose-1 phosphate and aberrant glycosylation GALT deficiency in this invertebrate. Studies in human patients led some investigators to propose that aberrant signaling pathways, notably phosphatidylinositol signaling (Berry 2011; Coss et al 2014), and defective glycosylation secondary to the accumulation of toxic galactose metabolites and deficiency of UDP-galactose are responsible for the neurological damages observed in these patients (Maratha et al 2016; Maratha et al 2016). Yet, it is important to realize that these mechanisms are not mutually exclusive and that they may act at different times during the central nervous system (CNS) development.…”
Section: Introductionmentioning
confidence: 99%
“…This is because such changes are well-documented in clinical studies of patients with GALT-deficiency classic galactosemia. Indeed, classic galactosemia is known as a secondary congenital disorder of glycosylation (CDG) because of glycosylation defects detected in patient cells [15,[56][57][58][59][60][61][62], which were attributed to decreased UDP-hexose contents [63][64][65][66]. Similarly, Itkonen and coworkers showed that siRNA targeting AGX1/UAP1 gene in PC3 cells led to increased sensitivity to tunicamycin treatment in cultured prostate cancer cells, as well as over 60% decrease in UGP-GlcNAc and UDP-GalNAc [19].…”
Section: Discussionmentioning
confidence: 99%
“…An over restricted galactose diet impairs myelin synthesis secondary to a deficit of galactolipids (galactocerebrosides) and glycoproteins, that is hypoglycosilated because of increased production of nongalactosylated or mono-galactosylated proteins [4,9,[11][12][13]. It has been observed In Vivo that the increased levels of galactose 1-phosphate inhibit glucose pyrophosphorylase reducing UDPglucose/galactose and responsible for impaired glycosylation of proteins and lipids, such problems are different between individual, because the activation of secondary pathways to metabolize galactose can be epigenetic regulated and depend on the individual's genetic characteristics [9,12].…”
Section: Glycosylation Impairmentmentioning
confidence: 99%
“…The treatment goal to maintain galactose 1-phosphate levels below 5 mg/dl with food containing with galactose content of less than 25 mg/100 gr is the backbone of the over restricted diet but is responsible for the impaired glycosylation of proteins leading to decreased white matter synthesis and the posterior neurological symptoms; and increased levels of galactose 1-phosphate are prone to induce oxidative stress and caused neurotoxicity [2][3][4][11][12][13][17][18][19].…”
Section: Conclusion: Over Restricted Diet or Notmentioning
confidence: 99%